2021
DOI: 10.3390/math9080896
|View full text |Cite
|
Sign up to set email alerts
|

Control Method of Flexible Manipulator Servo System Based on a Combination of RBF Neural Network and Pole Placement Strategy

Abstract: Gravity and flexibility will cause fluctuations of the rotation angle in the servo system for flexible manipulators. The fluctuation will seriously affect the motion accuracy of end-effectors. Therefore, this paper adopts a control method combining the RBF (Radial Basis Function) neural network and pole placement strategy to suppress the rotation angle fluctuations. The RBF neural network is used to identify uncertain items caused by the manipulator’s flexibility and the time-varying characteristics of dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 31 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…where ξ a1 and ω a1 denote the damping coefficient and the natural frequency coefficient of the poles. According to Equation (22), Equation ( 23) can be obtained.…”
Section: Controller Parameter Tuning Methods Based On Pole Placement ...mentioning
confidence: 99%
See 2 more Smart Citations
“…where ξ a1 and ω a1 denote the damping coefficient and the natural frequency coefficient of the poles. According to Equation (22), Equation ( 23) can be obtained.…”
Section: Controller Parameter Tuning Methods Based On Pole Placement ...mentioning
confidence: 99%
“…Under the literature [22], the expressions of the flexible load deformation could be obtained, as shown in Equation (). {w()x,tgoodbreak=bold-italicϕ()xbold-italicw()tgoodbreak=i=1ϕi()xwi()t,truew¨()tbold-italicw()tgoodbreak=goodbreak−italicEIϕ4()xitalicρAbold-italicϕ()xgoodbreak=goodbreak−bold-italicϑ,bold-italicϑbold-italicgoodbreak=[]ω120.5emω220.5em0.5emω2,ϕi()xgoodbreak=ch()βixgoodbreak−cos()βixgoodbreak+ςi()sh()βixgoodbreak−sin()βix,ςigoodbreak=goodbreak−sh()βilsin()βilch()βil+cos()βil,ωigoodbreak=βi2EIρA, where bold-italicϕ()x and bold-italicw()t denote the modal function and the modal coordinate; ρ , A , and EI denote the volume density, the flexible load cross‐section area, and the flexural rigidity; l denotes the flexible load length; ω i denotes the modal frequency; and β i denotes the characteristic roots of modal function equations.…”
Section: Mathematical Model Of a Dual Flexible Servo Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In practical application, the kinetic parameters of the object are often unknown, or only the nominal model is known, 16 which limits the application of the computed torque method. Since it has the property of approximating any nonlinear function, 17 the RBFNN can be used to approximate the unknown parameters of the kinetic model.…”
Section: Design Of Master Controllermentioning
confidence: 99%
“…To obtain the transfer function of the double flexible system is also the premise of the control stability of the servo system. According to the literature [25], it can be concluded that the influence of second-order modes on system output is only 1% of that of first-order modes. Therefore, only the first-order modal function of the system can be taken, and the transfer function of the system can be obtained according to Equation (22), as shown in Equation (23).…”
Section: Transfer Function Of Two Flexible Body Systemmentioning
confidence: 99%